2018
DOI: 10.1371/journal.pone.0194172
|View full text |Cite|
|
Sign up to set email alerts
|

Genetic variation and diversity in 199 Melilotus accessions based on a combination of 5 DNA sequences

Abstract: Melilotus is an important genus of legume plants and an herbage with excellent nitrogen fixation; it can tolerate extreme environmental conditions and possesses important medicinal value. However, there is limited genetic information about the genus; thus, we analysed four chloroplast loci (rbcL, matK, psbA-trnH and trnL-F) and one nuclear region (ITS) to determine the genetic diversity of 199 accessions from 18 Melilotus species. The rbcL and matK sequences were highly conserved, whereas the trnL-F and ITS se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…The results for genetic variation including nucleotide and haplotype diversity for both its regions showed that there were 104 and 89 polymorphic sites for its1 and its4 respectively, resulting in haplotype diversity of 0.972±0.064 and 0.917±0.092 and nucleotide diversity of 0.174±0.071 and 0.231±0.027 for its1 and its4 regions, respectively. This was in line with the findings of Zhang et al, (2018) where a haplotype and nucleotide diversity of 0.86 and 0.0087 was reported in 199 accessions of Melilotus species.…”
Section: Discussionsupporting
confidence: 93%
“…The results for genetic variation including nucleotide and haplotype diversity for both its regions showed that there were 104 and 89 polymorphic sites for its1 and its4 respectively, resulting in haplotype diversity of 0.972±0.064 and 0.917±0.092 and nucleotide diversity of 0.174±0.071 and 0.231±0.027 for its1 and its4 regions, respectively. This was in line with the findings of Zhang et al, (2018) where a haplotype and nucleotide diversity of 0.86 and 0.0087 was reported in 199 accessions of Melilotus species.…”
Section: Discussionsupporting
confidence: 93%